Viral pathogenesis of SARS-CoV-2 infection and male reproductive health. Issue 1 (20th January 2021) - Roychoudhury, Shubhadeep; Das, Anandan; Jha, Niraj Kumar; Kesari, Kavindra Kumar; Roychoudhury, Shatabhisha; Jha, Saurabh Kumar; Kosgi, Raghavender; Choudhury, Arun Paul; Lukac, Norbert; Madhu, Nithar Ranjan; Kumar, Dhruv; Slama, Petr
Abstract : Abstract : Coronavirus disease 2019 (COVID-19) has emerged as a new public health crisis, threatening almost all aspects of human life. Originating in bats, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmitted to humans through unknown intermediate hosts, where it is primarily known to cause pneumonia-like complications in the respiratory system. Organ-to-organ transmission has not been ruled out, thereby raising the possibility of the impact of SARS-CoV-2 infection on multiple organ systems. The male reproductive system has been hypothesized to be a potential target of SARS-CoV-2 infection, which is supported by some preliminary evidence. This may pose a global threat to male fertility potential, as men are more prone to SARS-CoV-2 infection than women, especially those of reproductive age. Preliminary reports have also indicated the possibility of sexual transmission of SARS-CoV-2. It may cause severe complications in infected couples. This review focuses on the pathophysiology of potential SARS-CoV-2 infection in the reproductive organs of males along with their invasion mechanisms. The risks of COVID-19 on male fertility as well as the differences in vulnerability to SARS-CoV-2 infection compared with females have also been highlighted.